Comparison of the efficacy of spironolactone versus flutamide in the treatment of hirsutism - (:unkn) unknown (My University, 1994)
OBJECTIVE: To compare the efficacy of two antiandrogens, spironolactone and flutamide, in the treatment of hirsutism. PATIENTS, PARTICIPANTS: Twenty women with idiopathic hirsutism were randomized to receive either flutamide or spironolactone. DESIGN: Twenty hirsute women were recruited from patients presenting to the hirsutism clinic in Marmara University, Istanbul. Each patient underwent a complete medical and gynecological examination as well as endocrine profile, hematologic, hepatic, and renal function analyses. Hirsutism scores were determined according to the Ferriman-Gallwey scoring system. These tests were then repeated at 3, 6, and 9 months of therapy. Ten patients received 250 mg of flutamide two times per day, and 10 patients received 100 mg of spironolactone for 9 months. RESULTS: Ferriman-Gallwey scores were decreased significantly in both groups at the end of 9 months. The percent of change in hirsutism scores in flutamide and spironolactone group were as follows: 26.4% and 20.9% at 3 months; 39.5% and 32.9% at 6 months; and 46.4% and 39.6% at 9 months, respectively. There was a trend toward a better response with flutamide that did not achieve significance. None of the hormonal parameters changed significantly during this period of time. Irregular bleeding was observed in five patients (50%) of the spironolactone group, whereas none of the patients in the flutamide group experienced menstrual irregularity. Conversely, dry skin and increased appetite were experienced by two patients (20%) in the flutamide group but not in the spironolactone group. CONCLUSION: These data suggest that both spironolactone and flutamide were similarly effective in treatment of hirsutism, and the pure antiandrogen flutamide is a safe and effective alternative in treatment.
Keywords: Adult; Female; Humans; Adolescent; Follicle Stimulating Hormone; Luteinizing Hormone; Hirsutism; Spironolactone; Testosterone; Flutamide; Dehydroepiandrosterone; Dehydroepiandrosterone Sulfate